The practice of the Constitutional Court of the Russian Federation in the sphere of copyright and related rights - Lepeshin, Dmitry A.; Petkilev, Petr I. (Journal of the Belarusian State University. Law, 2024)
Intellectual property right continues its rapid development. Legislative regulation of intellectual property rights continues, laid down in the Constitution of the Russian Federation right of every person to freedom of artistic, scientific, technical and other types of creativity, teaching. The Constitutional Court of the Russian Federation, being the highest judicial body of constitutional control, resolves cases on the compliance of certain forms of law with the Constitution of the Russian Federation. The positions of the judicial acts adopted as a result of this activity are of great importance for judicial activity and for law enforcement practice. This study is aimed at analysing and summarising of judicial acts adopted by the Constitutional Court of the Russian Federation on issues about copyright and related rights.
Keywords: copyright; related rights; Constitutional Court of the Russian Federation; intellectual property